The implementation of religious moderation education for students at sma negeri 13 oku, south sumatra - Faozan; Ayu Yusfika; Inti Pita Sari (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to analyze the influence of Islamic parenting on the formation of religious values in early childhood at PAUD Al-Azhar Baturaja OKU. Using a quantitative approach with an explanatory survey design, the study involved 40 parents of students as respondents. Data were collected through standardized questionnaires and analyzed using descriptive statistics and linear regression. The results showed that Islamic parenting had a significant effect on children's religious values (r = 0.672; p < 0.01), with a contribution of 45.2% (R² = 0.452). The majority of parents (60%) applied Islamic parenting in the moderate category, with the aspect of exemplary worship being the most dominant. Children's religious values showed an even distribution with 47.5% in the moderate category and 32.5% in the high category, where consistency of prayer was the strongest indicator. Qualitative findings revealed three main mechanisms of influence: (1) religious modeling through dual parent-teacher exemplars, (2) structured habits at school, and (3) social reinforcement. Implementation challenges include the influence of digital media (72% of respondents), generation gaps (65%), and limited parenting literacy (60%). This study concludes that Islamic parenting is a crucial factor in the formation of religious values in early childhood, with effectiveness depending on family-school synergy and adaptation to the challenges of the digital era. Practical implications include recommendations for the development of contextual parenting modules and optimization of value habituation programs in Islamic-based PAUD.